2012
DOI: 10.1002/adhm.201200161
|View full text |Cite
|
Sign up to set email alerts
|

Capture, Enrichment, and Mass Spectrometric Detection of Low‐Molecular‐Weight Biomarkers with Nanoporous Silicon Microparticles

Abstract: Mining the disease information contained in the low-molecular-weight range of a proteomic profile is becoming of increasing interest in cancer research. This work evaluates the ability of nanoporous silicon microparticles (NPSMPs) to capture, enrich, protect, and detect low-molecular-weight peptides (LMWPs) sieved from a pool of highly abundant plasma proteins. The average pore size and porosity of NPSMPs are controlled by the electrochemical preparation conditions, and the critical parameters for admission or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…136 Another mass spectrometric sensor was fabricated by Wu's group using nanoporous silicon microparticles to capture, enrich, protect, and detect low-molecularweight peptides sieved from a pool of highly abundant plasma proteins in a colorectal cancer patient's serum. 137 Some magnetic and mechanical assays have also been used for cancer protein biomarker evaluation. [138][139][140][141] However, these techniques all require expensive equipment, sophisticated instrumentation, and specially trained technical personnel, which goes against the basic requirements of point-of-care testing that instead requires compact, robust, and inexpensive instruments.…”
Section: Cancer Protein Biomarkersmentioning
confidence: 99%
“…136 Another mass spectrometric sensor was fabricated by Wu's group using nanoporous silicon microparticles to capture, enrich, protect, and detect low-molecularweight peptides sieved from a pool of highly abundant plasma proteins in a colorectal cancer patient's serum. 137 Some magnetic and mechanical assays have also been used for cancer protein biomarker evaluation. [138][139][140][141] However, these techniques all require expensive equipment, sophisticated instrumentation, and specially trained technical personnel, which goes against the basic requirements of point-of-care testing that instead requires compact, robust, and inexpensive instruments.…”
Section: Cancer Protein Biomarkersmentioning
confidence: 99%
“…In most cases, a combination of techniques is used. Recently, more unconventional techniques to purify and enrich serum proteins prior to MS detection were described, including the use of nanoporous silicon microparticles or mesoporous silica chips .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that nanoporous Si microparticles (NPSMPs) with a suitable pore size could not only capture LMWPs from serum samples, but also effectively exclude proteases (such as trypsin) and protect the captured peptides from degradation. 8 The goal of this study is to further elucidate, with the assistance of this nanotechnology, whether the peptide information in the original serum sample can be retained under different storage conditions.…”
mentioning
confidence: 99%
“…Fourier transform reflective interferometric spectroscopy was employed for establishing the relationship between cut-off M W and critical porosity of porous Si. 8 The surface of NPSMPs was modified with undecylenic acid, which can improve the stability of NPSMPs, as well as their affinity for peptides. Compared with nanoporous silica particles, 9 mesoporous silica chips or films, 10 mesoporous carbon, 11 and smart hydrogels 12 that have been employed for capturing LMWPs from serum samples, the pore diameter of pSi can be precisely tailored by electrochemical etching parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation